Potential of Pigmented Rice Enriched with Kappa-Carrageenan and Anthocyanin Extract For Glycaemic Property Improvements in Diabetic Rats - Nurhidajah; Astuti, Mary; Astuti, Mary; Sardjono; Murdiati, Agnes (Pakistan Journal of Nutrition, 2016)
The objective of this study was to evaluate the glycaemic property of diabetic rats after consumption of enriched pigmented rice. During the experiment, thirty 2.5-month-old male Wistar rats with 175-250 g body weights were divided into 6 groups (n = 6) and fed Mandel Handayani pigmented rice enriched with 2% kappa-carrageenan and anthocyanin extract from black rice (5 ml/100 g pigmented rice) and standard feed AIN 93 for maintenance. After 5 days of adaptation, diabetes was induce using STZ and nicotinamide and treatment was started 5 days afterwards for 6 weeks. The observed parameters were feed remains and efficiency, body weight, blood glucose level, serum insulin assayed using a rat ELISA insulin kit and Homa IR and Homa β analyses. The results showed that both pigmented rice and kappa-carrageenan and anthocyanin-enriched pigmented rice improved the glycaemic properties of diabetic rats, as indicated by increases in rat body weight of between 10.14 and 11.94%, with feed efficiency ranging between 13.62 and 17.39%, reduced and stabilized blood glucose levels, increased insulin levels, reduced insulin resistance (HOMA IR) and improved pancreatic β cell function (HOMA β).